With Age Comes Wisdom - Worthy, Darrell A.; Gorlick, Marissa A.; Pacheco, Jennifer L.; Schnyer, David M.; Maddox, W. Todd (Psychological Science, 2011)
In two experiments, younger and older adults performed decision-making tasks in which reward values available were either independent of or dependent on the previous sequence of choices made. The choice-independent task involved learning and exploiting the options that gave the highest rewards on each trial. In this task, the stability of the expected reward for each option was not influenced by the previous choices participants made. The choice-dependent task involved learning how each choice influenced future rewards for two options and making the best decisions based on that knowledge. Younger adults performed better when rewards were independent of choice, whereas older adults performed better when rewards were dependent on choice. These findings suggest a fundamental difference in the way in which younger adults and older adults approach decision-making situations. We discuss the results in the context of prominent decision-making theories and offer possible explanations based on neurobiological and behavioral changes associated with aging.